Using New Technologies in Healthy Lifestyle Interventions Targeted at Children: The Case of the Netherlands - Háša, Marek (Univerzita Karlova, Fakulta sociálních věd, 2018)
New technologies such as social media or mobile games are often listed among the main contributors to the ever-increasing obesity rates among children. Paradoxically, the same technologies also bring potential to enhance the effectivity of healthy lifestyle interventions targeted at children. This thesis investigated the approach of the creators of such interventions towards the use of new technologies. The author devoted his attention to downstream social marketing interventions realised in the Netherlands because of the country's low youth obesity rates and exceptional position in the latest innovation rankings. The central objective of this instrumental multiple case study research was to reveal the benefits and limitations of the researched practice as perceived by the interventions' creators. Studying available documents and conducting four semi-structured interviews with the creators enabled the author to reconstruct the contexts and strategies of four Dutch healthy lifestyle interventions promoting exercise and healthy sleep and nutrition among children. The results indicated that the creators indeed regarded new technologies as a threat to children's physical and mental well-being; nevertheless, they also accepted them as an inevitable part of today's media environment and aimed to. Nové technologie, jako jsou sociální sítě nebo mobilní hry, jsou často viněny z přispívání k neustále rostoucímu procentu obézních dětí. Ty samé technologie však paradoxně skrývají velký potenciál pro kampaně propagující zdravý životní styl mezi dětmi. Předmětem této práce byl přístup tvůrců takových kampaní k využití nových technologií. Autor se zaměřil na kampaně sociálního marketingu, které mají za cíl měnit návyky jednotlivců. Nizozemsko bylo pro svou nízkou prevalenci dětské obezity, a naopak velmi vysoké postavení ve světovém žebříčku inovativnosti vybráno jako země, jejíž kampaně by mohly poskytnout cennou inspiraci pro sociální marketéry z Česka i jiných evropských zemí. Hlavním cílem této mnohonásobné instrumentální případové studie bylo odhalit, jaké výhody a limitace využití nových technologií spatřovali sami tvůrci kampaní na podporu zdravého životního stylu u dětí. Na základě prostudování dostupných dokumentů a realizace polostrukturovaných rozhovorů s tvůrci sestavil autor případové studie čtyř nizozemských kampaní propagujících cvičení a zdravý spánek a stravu mezi dětmi. Výsledky výzkumu ukázaly, že autoři těchto kampaní skutečně vnímali nové technologie jako hrozbu pro fyzické i psychické zdraví dětí. Zároveň však tyto technologie považovali za neodlučitelnou součást dnešní. Katedra marketingové komunikace a public relations Department of Marketing Communication and Public Relations Fakulta sociálních věd Faculty of Social Sciences